Pengaruh Penggunaan Media Sketchfab terhadap Hasil Belajar Sistem Pernapasan Kelas V SDN 2 Kapuan - Galuh Sekar Ajijatitesih; Gita Adinda Sari; Ika Dian Rahmawati (Lembaga Yasin AlSys, 2026)
The suboptimal learning outcomes of students on the respiratory system topic and the limited use of three-dimensional (3D) digital learning media in elementary schools indicate the need for more concrete, interactive, and contextual media innovation. This study aims to examine the effectiveness of using the Sketchfab platform as a learning medium in improving IPAS learning outcomes on the human respiratory system topic in Grade V at SDN 2 Kapuan. This study used a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample was determined using saturated sampling by involving all 27 Grade V students. Data were collected through learning outcome tests, observation sheets, and documentation, then analyzed using descriptive and inferential statistics with the assistance of SPSS software. The normality test results showed that the data were not normally distributed; therefore, hypothesis testing was conducted using the nonparametric Wilcoxon Signed Ranks Test. The results showed an increase in the average learning outcome score of 27.67 points, from 41.63 in the pretest to 69.30 in the posttest. The Wilcoxon test results obtained a Z value of -4.350 with an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), indicating that the use of Sketchfab media had a significant effect on students’ learning outcomes. The conclusion of this study affirms that 3D object-based interactive Sketchfab media is effective for improving elementary school students’ IPAS learning outcomes on the human respiratory system topic. These findings imply the importance of integrating 3D visual technology as a learning strategy to help teachers present abstract material in a more concrete, interactive, and appropriate manner according to learning needs in the digital era.